Pengaruh Tekanan Eksternal, Akuntabilitas, Ketidakpastian Lingkungan, dan Pengendalian Internal terhadap Penerapan Transparansi Pelaporan Keuangan (Studi Empiris pada OPD Kota Pontianak) - Khairunnisa, Dhea Nanda (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the effect of external pressure, accountability, environmental uncertainty, and internal control on the implementation of financial reporting transparency in Regional Apparatus Organizations (OPD) of Pontianak City. This research uses a quantitative approach with primary data collected through questionnaires. The population consists of OPD units in the form of government departments and the Regional Financial and Asset Management Agency (BKAD) of Pontianak City. Using purposive sampling, this study obtained 59 respondents from 16 OPDs. Data were analyzed using multiple regression analysis with SPSS. The results indicate that external pressure, accountability, and environmental uncertainty have a positive and significant effect on the implementation of financial reporting transparency. Meanwhile, internal control does not have a significant effect on financial reporting transparency. These findings indicate that external institutional demands, accountability mechanisms, and environmental dynamics play important roles in encouraging transparency practices in local government financial reporting.